Transmitting Light Through Biocompatible and Biodegradable Drug Delivery Micro Needles - Coppola, Sara; Vespini, Veronica; Nasti, Giuseppe; Ferraro, Pietro (IEEE journal of selected topics in quantum electronics, 2021)
The use of micro-needle for advanced self-administration and cutaneous therapy still represent a desired solution that could open towards still unexplored medical market. Recently we have developed a fabrication method that avoids one of the major drawbacks of conventional processes by using a mold-less direct fabrication approach based on electro-drawing of microneedle from sessile drops of biodegradable polymer. The method is completely contact-free, simple and low-cost. On the other side, the intriguing future developments of biodegradable microneedles is the possibility to functionalize and use the microneedles for phototherapy, and/or light assisting for in-situ drug activation or other functionalization that could require light delivery. Here we show that it is possible to fabricate microneedles able to focus and transmit light. In particular, we report how an electro-drawn microneedle, realized by a single-step process, can be used as a sort of light guiding micro-photonic element at the aim to delivery light form its tip. We demonstrate the light guiding properties of these conical structures showing preliminary modelling results combined with the experimental optical characterization. We believe that the proposed approach could be further exploited and could inspire future fabrication of smart nanobiophotonic devices combing multiple functionalities for implantable medicine and drug-delivery applications.